Personal Approach in Islamic Religious Education Learning at Muhammadiyah 1 Middle School, Purwokerto - Anah, Dhiya Roiha; Mayasari, Novi (Indonesian Academy of Social and Religious Research (IASRR), 2025)
Personal Approach as an alternative to improve the quality of Islamic Religious Education (PAI) learning. This approach works through the internalization of universal Islamic values, strengthening the spiritual dimension of students, examples of good behavior from teachers, and open two-way communication. This study aims to understand the planning, implementation, and evaluation of the application of the Personal Approach in Islamic Religious Education (PAI) learning at SMP Muhammadiyah 1 Purwokerto. This study uses a case study method with a qualitative approach to examine SMP Muhammadiyah 1 Purwokerto which is located in Banyumas Regency. Participants in this study were PAI Teachers, Principals, and Students at the school. The results of the study on the Personal Approach in Islamic Religious Education learning at SMP Muhammadiyah 1 Purwokerto identified three stages in its implementation: 1) Planning Stage, the school holds a preparatory workshop before the new school year begins 2) Implementation Stage, teachers approach students who are having difficulties one by one and then help solve the problems 3) Evaluation Stage, there are advantages and disadvantages in this approach and teachers handle it by holding remedial or providing learning outside the classroom to students.